The war against extensively drug resistant Mycobacterium tuberculosis: intelligence acquisition - Jacobs, William (Henry Stewart Talks, 2009)
Tuberculosis today, Susceptibility pattern, Hospital acquired XDR-TB, XDR-TB realities, TB sanatorium evolution, Development of knowledge of TB, Causes of consumption: Samuel Sheldon Fitch and Edward Livingston Trudeau, Molecular Koch's postulate, Why no genetics for M. tuberculosis?, Mycobacteriophage delivery vectors, Genetics = new knowledge, Bacille Calmette and Guerin (BCG), Reconstruction of BCG, Primary attenuation of BCG, By understanding how M. Tuberculosis evades immunity it should be possible to make better vaccines than BCG